HELICOPTER PARENTING STYLE "IMPACT ON COMMUNICATION SKILLS OF ALPHA GENERATION CHILDREN IN INDONESIA" - Ifan Awanda; Septika laily Anti; Miranda Yustikasari; Selly Nurlela Sari (Indonesian Journal of Education and Youth Development, 2025)
This research examines the impact of helicopter parenting on the development of communication skills in Generation Alpha children (4-7 years old) in urban areas of Indonesia. This research aims to determine the impact of helicopter parenting styles on children's development and communication skills. The research method uses an explanatory sequential mixed-methods approach involving 30 families from Lampung. Data was collected through the Helicopter Parenting Scale questionnaire (α=0.82), structured observation, and in-depth interviews. The results of the quantitative analysis show a significant negative correlation between helicopter parenting intensity and turn-taking ability (r=-0.62, p<0.05) and speech acts (r=-0.51, p<0.05). Qualitative findings identified three distinct communication patterns: (1) ghost scripting, (2) avoidance strategy, and (3) filler speech dominance. This study recommends the "Guided Autonomy Parenting" intervention program to mitigate the negative effects of helicopter parenting.